Aktivitas Ekstrak Gorgonia Sp Dengan Pelarut Yang Berbeda Terhadap Tingkat Kesegaran Ikan Tembang (Sardinella Fimbriata) Selama Penyimpanan Basah - Idanti, Sri; Henggu, Krisman Umbu (JURNAL PENGOLAHAN PERIKANAN TROPIS, 2024)
Tembang fish (Sardinella fimbriata) is a very important fish resource and has economic value. Apart from being consumed, tembang fish (Sardinella finbriata) is usually used as raw material for processed fish in the form of salted fish and dried fish. However, tembang fish is known to be a perishable commodity. Therefore, a preservation process is needed that is able to maintain the freshness quality of the fish during fresh storage. Gorgonian sp. is one of the animals that has a number of bioactive components which are thought to have an impact on the durability of fresh fish. The results of the study showed that the average TVB value of fresh tembang fish in the control treatment ranged from 14.01%-24.51% (mgN/100g), distilled water extract 11.67%-21.01% (mgN/100g), and methanol 12.84% -15.17% (mgN/100g). This shows that the use of methanol on the activity of Gorgonian sp extract. in maintaining fish freshness, it is more optimal than distilled water treatment and control (without treatment). Meanwhile, the organoleptic quality of fresh fish treated with Gorgonian sp extract. During the 8 hours of observation it was categorized as fresh (still fit for consumption) with an average organoleptic quality ranging from 10-6 (very fresh to the point of still being fit for consumption)